FOLIN–CIOCÂLTEU METHOD FOR DETERMINATION OF TOTAL POLYPHENOLS IN ONION - Viktorija Sokolovska, Mirjana S. Jankulovska (Faculty of Agricultural Sciences and Food - Skopje, 2022)
Onion is one of the most important crop in the world and the richest source of polyphenols. Polyphenols are organic compounds that are naturally present in onions and influence to its quality. The content of polyphenols depends on different factors. In this research determination of total polyphenols and flavonoids in two Macedonian local populations of onions was done by UV-Vis spectroscopy. The extraction of polyphenols from onions was performed with 60% methanol, while time for extraction was 120 minutes. Required time for completion of the reaction between polyphenols and Folin – Ciocâlteu reagent was examined. The total polyphenolic content was determined by the Folin – Ciocâlteu method with gallic acid as a reference standard. The obtained results were presented as mg GAE/100 g onion. Furthermore, the content of flavonoids in analyzed onions was determined with quercetin as a reference standard. The results were presented as mg QE/100 g onion. Polyphenols and flavonoids were determined in the onions’ extracts immediately after extraction and in the extracts stored 18 hours in a refrigerator at 4 °C. The results showed that there is no significant difference in content of polyphenols in analyzed onions, while the flavonoid content was higher in a population Melnik.
Keywords: Flavonoids, Folin–Ciocâlteu method, onion, polyphenols, UV-Vis spectroscopy